2022
DOI: 10.1007/s11694-022-01627-4
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocessing of pineapple waste biomass for sustainable production of bioactive compounds with high antioxidant activity

Abstract: The effect of temperature, moisture content and pH during solid-state fermentation (SSF) of MD2 pineapple peel with Rhizopus oryzae (MUCL 28168) was evaluated on the release of bioactive compounds with antioxidant capacity. Applying a central composite design, it was found that temperature had a significant effect (p < 0.05) on the total phenolic content and DPPH antioxidant activity while for the ABTS radical elimination activity, the factor that presented a significant effect was the pH (p < 0.05); as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 85 publications
3
7
1
Order By: Relevance
“…The presence of alkaloid group compounds in the FU sample is possible due to the soaking/maceration of pineapple fruit in Arak Bali during the manufacturing process. This is in accordance with previous studies which stated that alkaloids are a class of secondary metabolite compounds contained in pineapple (Babajide et al, 2013;Hikal et al, 2021;Nurdalilah et al, 2018;Rivera et al, 2022;Rustini et al, 2022;Saleh et al, 2021;Sayago-Ayerdi et al, 2021;VH et al, 2021).…”
Section: Qualitative Test Alkaloidssupporting
confidence: 94%
See 2 more Smart Citations
“…The presence of alkaloid group compounds in the FU sample is possible due to the soaking/maceration of pineapple fruit in Arak Bali during the manufacturing process. This is in accordance with previous studies which stated that alkaloids are a class of secondary metabolite compounds contained in pineapple (Babajide et al, 2013;Hikal et al, 2021;Nurdalilah et al, 2018;Rivera et al, 2022;Rustini et al, 2022;Saleh et al, 2021;Sayago-Ayerdi et al, 2021;VH et al, 2021).…”
Section: Qualitative Test Alkaloidssupporting
confidence: 94%
“…This is because the soaking/maceration process of the pineapple during the process of making the FU sample allows the tannin compounds to be extracted from the pineapple and dissolved in the pineapple infused Arak Bali. This is consistent with the results of previous studies which proved that pineapple contains various secondary metabolites such as alkaloids, flavonoids, phenols, tannins, and terpenoids (Babajide et al, 2013;Hikal et al, 2021;Nurdalilah et al, 2018;Rivera et al, 2022;Rustini et al, 2022;Saleh et al, 2021;Sayago-Ayerdi et al, 2021;VH et al, 2021).…”
Section: Quantitative Analysis Tanninssupporting
confidence: 93%
See 1 more Smart Citation
“…One notable avenue in the realm of green synthesis involves the utilization of PgP and PnP as potent bioreducing and capping agents for the synthesis of AgNPs. PgP and PnP, often regarded as agricultural waste, have been recognized for their rich content of bioactive compounds, including polyphenols, favonoids, and enzymes [6]. Tese bioactive constituents play a pivotal role in the reduction of silver ions and stabilization of the resulting nanoparticles, rendering the synthesis process not only environmentally benign but also cost-efective.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, core waste could be converted into alcoholic beverages or vinegar [ 8 ]. In addition, it has been reported that pineapple waste could be used as a substrate for the production of cellulose, methane, ethanol, citric acid, antioxidant compounds, and bioactive compounds, including a biopolymer of PHAs [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Recently, alternative means of pineapple waste utilisation were its uses as sources of proteolytic enzymes in which the different parts of pineapple would present different bromelain and other cysteine protease enzymes [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%